Valgus stability is enhanced by flexor digitorum superficialis muscle contraction of the index and middle fingers - Hoshika, Shota; Nimura, Akimoto; Takahashi, Norimasa; Sugaya, Hiroyuki; Akita, Keiichi (Journal of orthopaedic surgery and research, 2020)
Background Flexor digitorum superficialis (FDS) muscle provides dynamic stabilization and medial elbow support for ulnar collateral ligament (UCL). The FDS contraction significantly affects the medial joint distance (MJD) through grip contraction. However, it remains unclear whether FDS activity alone contributes to medial elbow stability, or together with the activation of the flexor digitorum profundus during grip contraction, and which finger’s FDS is the main contributor to elbow stability. We investigated the resistive effects of isolated FDS contraction in individual fingers against valgus stress in the elbow joint using stress ultrasonography (US). Methods We investigated 17 healthy males (mean age, 27 ± 5 years). Valgus stress US was performed using the Telos device, with the elbow at 30° flexion. MJD was measured for each arm during 3 separate conditions: at rest (unloaded), under valgus load (50 N) (loaded), and under valgus load with FDS contracted in individual fingers (loaded-contracted). Results MJD was significantly longer when loaded (5.4 ± 0.4 mm) than unloaded (4.1 ± 0.2 mm, P = 0.007) or loaded-contracted (4.6 ± 0.3 mm, P = 0.003) for each finger. When loaded-contracted, MJD differed statistically between the index and ring fingers ( P = 0.03) and between the middle and ring fingers ( P = 0.04). However, the difference between the index and middle fingers was not statistically significant ( P = 0.08). Conclusions Individual FDS contraction, particularly of the index and middle fingers, contributes most to stabilization against valgus stress. Thus, injury care programs should incorporate FDS exercises of these fingers.